Sprawozdanie z Międzynarodowej Konferencji „International relations and human rights”, Tallinn 11–13 marca 2016 r. - Sadowa, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In the paper Author recounts scientific conference – International Relations and Human Rights, which took place in Tallinn in March 2016. Author not only summarizes the event, but also shows aims and functioning of the Nordic Summer University – an organization which initiated the conference
Keywords: sprawozdania; konferencje; Tallinn (Estonia); Nordic Summer University; prawa człowieka; migracje